Financial citizenship barriers among Muslim micro-entrepreneurs in Ilorin, Nigeria: a factorial invariance analysis - Adewale, Abideen Adeyemi; Pramanik, Ataul Huq; Mydin Meera, Ahamed Kameel (Islamic Research and Training Institute, 2014)
This study examines the factors that explain the lack of financial citizenship among selected respondent poor households in the inner city of a densely Muslim populated area. Specifically, Ilorin, Kwara State, North Central geo-political zone of Nigeria was the study area in this regard. Data elicited via a survey questionnaire was analysed using both the SPSS 17.0 and Amos 17.0 software. Based on both the exploratory and confirmatory factor analyses, the study revealed that the barrier factors can be divided into two broad categories. While debt phobia, religion, financial complacency, and cultural capital explain voluntary exclusion, affordability and eligibility factors explain the involuntary financial exclusion barriers. The results indicate that the lack of financial citizenship is explained by both lack of access and unwillingness to patronise certain sources of funds. Factorial indifference was also found along demographic divides of the respondents except for age and primary occupation in which case no difference was found between the trading and non-trading micro entrepreneurs.